Analysis of Three Actors: Roles of Government, Private Sector, and University toward Startup Growth in Yogyakarta - Cinintya Audori Fathin; Ashilly Achidsti; Dimas Indra Priambodo (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2016)
Information, communication, and technology advancements in 21st century encourage startups to innovate and develop their business further. Because it’s an ICT based business which is supported by the existence of internet, this kind of business starts to become borderless. As a result, the distributions of the products start to become unlimited. The conveniences offered by these advancements invite more ICT based product developers. The positive impact as a result of that such as more new jobs, easier way to access the markets, and also cheaper production cost with guaranteed profits. In addition to that, this of course also becomes an added value to the country because it increases Network Readiness Index and nation’s income from taxes. This research aims to analyze startup’s growth, in addition to its relation with related actors such as government, private sectors, and universities. Analysis on every actor will emphasize on their contribution to startup developments in Daerah Istimewa Yogyakarta directly or indirectly. In conclusion, there will be an illustration about how big the contributions and how close the actors are between startups and the three actors.